2009
DOI: 10.1590/s0100-83582009000100015
|View full text |Cite
|
Sign up to set email alerts
|

Características morfológicas de gramas em resposta à aplicação de trinexapac-ethyl

Abstract: RESUMO -O presente trabalho teve como objetivo avaliar os efeitos da aplicação de duas doses de trinexapac-ethyl sobre a morfologia das espécies de gramas São Carlos (Axonopus compressus), Batatais (Paspalum notatum), Santo Agostinho (Stenotaphrum secundatum) e Esmeralda (Zoysia japonica). Os gramados foram cortados à altura de 3 cm no início do experimento e 20 dias depois. Após cada corte, foram realizadas duas aplicações sequenciais de trinexapac-ethyl nas doses de 56,5 + 56,5 e 113,0 + 113,0 g ha -1 , além… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
1
7
0
2
Order By: Relevance
“…Table 4 that the application of trinexapac-ethyl reduced the average height of Bermuda grass (Cynodon dactylon), which reached values close to 50%, and all doses were effective and similar. These results corroborate those found by McCullough et al (2007), Costa et al (2009) andMaciel et al (2011). Regarding the number of flower stems, reductions were observed from the dose of 226 + 226 g ha was applied, that is to say, a reduction of 52%, 70%, 69% and 73%, respectively (Table 4).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Table 4 that the application of trinexapac-ethyl reduced the average height of Bermuda grass (Cynodon dactylon), which reached values close to 50%, and all doses were effective and similar. These results corroborate those found by McCullough et al (2007), Costa et al (2009) andMaciel et al (2011). Regarding the number of flower stems, reductions were observed from the dose of 226 + 226 g ha was applied, that is to say, a reduction of 52%, 70%, 69% and 73%, respectively (Table 4).…”
Section: Resultssupporting
confidence: 88%
“…Table 3 shows that the trinexapac-ethyl growth regulator, regardless of the dose and number of applications, significantly reduced the number and height of flower stems of the Japanese lawn grass; these reductions were less accentuated by the application of the 113 + 113 g ha for the height of these stems. Some studies have shown that, with the application of trinexapac-ethyl, there may be a decrease or delay in the emission of inflorescences, maintaining the aesthetics of the lawn for a longer time (Johnson, 1990;Fry, 1991;Costa et al, 2009;Mittlesteadt et al, 2009;Marchi et al, 2013b). Type II growth regulators, which is the case of trinexapac-ethyl, are not efficient in suppressing the emission of floral stems because they interfere with the biosynthesis of gibberellins, thereby reducing cell elongation (Marchi et al, 2013a;Marchi et al, 2014); however, in this study, with Japanese lawn grass, significant effects resulting from its application were observed at high doses.…”
Section: Resultsmentioning
confidence: 99%
“…Several research works have shown that trinexapac-ethyl when sequentially applied to TifEagle bermudagrass plants may retard and/or reduce the emission of inflorescences and prolong the lawn visual aspect making unnecessary a new mechanical plant cutting (JOHNSON, 1990;FRY, 1991;COSTA et al, 2009;MITTLESTEADT et al, 2009). McCullough et al (2007 reported a reduction of the order of 81% in the number of floral rachises when three doses equivalent to 50 g ai ha -1 of trinexapac-ethyl were applied at intervals of seven days on TifEagle bermudagrass (Cynodon dactylon × C. transvaalensis Burtt-Davy).…”
Section: Resultsmentioning
confidence: 99%
“…ha -1 . However, different results were reported by Costa et al (2009), who observed that the sequential application of trinexapac-ethyl (113 + 113 g a.i. ha -1 ) promoted reduction of only 28.5% in the emergence of flower rachises of P. notatum in the period of 70 days after the second application.…”
Section: Resultsmentioning
confidence: 72%